Fucoxanthin ameliorates Propionibacterium acnes-induced ear inflammation in mice by modulating the IκBα/NF-κB signaling pathway and inhibiting NF-κB nuclear translocation - Shan Jiang; Xiaoyan Peng; Yan Chen; Bingqi Dong; Hu Mao (PLoS ONE, 2025)
Background Acne vulgaris, a chronic inflammatory skin disorder, represents a pivotal research area in dermatology. Although fucoxanthin, a marine-derived carotenoid, displays potent anti-inflammatory activity, its therapeutic potential in acne pathogenesis remains underexplored. Objective This study investigates fucoxanthin’s effects on Propionibacterium acnes (P.acnes)-induced auricular inflammation in mice, focusing on its modulation of the IκBα/NF-κB signaling axis and inhibition of NF-κB nuclear translocation. Methods Inflammation in the ear of mice was induced using a P.acnes injection model. The anti-inflammatory effects of fucoxanthin were verified by evaluating the levels of erythema, pathological damage, and inflammatory factors in the mice ear. An in vitro model was constructed to explore the regulatory mechanism of IkappaBalpha (IκBα)/nuclear factor-kappaB (NF-κB) pathway by fucoxanthin. Results Fucoxanthin alleviated P. acnes-induced inflammatory pathology, reducing ear erythema. Mechanistically, it preserved IκBα stability, suppressed NF-κB nuclear translocation, and decreased proinflammatory cytokine production. Conclusion Fucoxanthin exerts anti-acne effects through coordinated inhibition of IκBα degradation and NF-κB nuclear translocation, establishing its potential as a targeted therapeutic agent for inflammatory acne.